ESTIMATING CROP PRODUCTION FUNCTION FOR SOME CROPS AT MOSUL AREA - Eman Hazim Sheet (Mesopotamia Journal of Agriculture)
Crop production function for some crops in Mosul area are estimated. These crops are wheat and legume، as winter crops ،and corn and cotton ، as summer crops. A computer model was constructed to program daily irrigation for the four crops under investigation in order to find the relative production of each crop. The simulation model is based on daily water balance analysis on 20 years of climatological data for the period 1980-2000. Daily soil moisture depletion is evaluated, the model predicts the data and amount of irrigation when the soil moisture depletion in the root zone exceeds the maximum level of percent allowable depletion. The model is designed to give maximum daily deficit, irrigation water through the growing season ,daily and seasonal effective rainfall and actual evapotranspiration and seaonal relative production. Two production functions، linear and quadratic were assumed, the first is between relative production and amount of seasonal irrigation, and the second relation is between relative production and actual evapotranspiration . It was also found that the difference between the linear and quadratic production function is small but the correlation coefficient for quadratic production function is more than that for the linear function. The computer model can be used to estimate crop production function for other crops by changing crop data.